Kurumsal iletişim yönetiminde ileribildirim - Kasar, Aslı (My University, 2020)
KURUMSAL İLETİŞİM YÖNETİMİNDE İLERİBİLDİRİMİlişki kavramının ve çift yönlü iletişimin öne çıktığı ve önemli olduğu günümüz koşullarında çift yönlülüğü sağlayan geribildirim kullanımı da büyük önem taşımaktadır. Ancak, günümüzde sosyal medyanın, dijital içeriğin ve mobil cihazların çoğalması, sürekli iletişim bekleyen hedef kitle, paydaş ve kamular oluşturduğu için bu talebi karşılamak için kurumlar, gittikçe daha da kısalan zaman çerçevelerinde, hedef kitleleri, paydaşları ve kamuları ile iletişimi sağlamak durumunda kalmaktadır. Ayrıca kurumlar, faaliyet gösterdikleri sistem içinde ekonomik, teknolojik, demografik, sosyal ve politik faktörlerden kaynaklanan sürekli değişen dış baskılar, kurumların iç sistemleri ve kontrol sistemleri üzerinde etkili olarak öngörülemeyen durumlara sebebiyet vermektedir. Bu öngörülemeyen durumlar ise kurumların faaliyetlerini etkileyebilmektedir. Bu neden ile sosyal bilimlerde araştırılmamış ve sadece tanımı yapılmış bir kavram olan ileribildirimi, halkla ilişkiler veya kurumsal iletişim literatürüne kazandırarak, günümüz koşullarında değişen paradigmaya, kurumların uyum sağlayarak iletişim süreçlerinde etkili ve başarılı olmaları amaçlanmaktadır.Bu kapsamda iki aşamalı olarak planlanan çalışmamızın ilk aşamasında literatür incelemesi kapsamında “geribildirim” kavramı yeniden tanımlanmakta ikinci aşamasındaysa, çalışmanın asıl konusunu oluşturan “ileribildirim” kavramı geliştirilerek, bu kavrama özgün bir katkı sunulmaya çalışılmaktadır.

THE FEEDFORWARD IN CORPORATE COMMUNICATION MANAGEMENTIn today’s conditions in which the concept of relationship and two-way communication have gained importance, the use of feedback that enables two-way communication is of much significance. However, as the proliferation of social media, digital content and mobile devices creates a target mass anticipating continuous communication, stakeholders and communities, institutions are supposed to enable the communication with their target masses, stakeholders and communities within the time that is shortening gradually in order to meet this demand. Also, the institutions lead significantly to some unforeseen situations on ever-changing external pressures, internal systems and control systems of the institutions resulting from economic, technological, demographical, social and political factors within the system in which they act and serve. These unforeseen situations may affect the activities of the institutions. Therefore feedforward, a concept that has only been defined but not analysed in social sciences, is intended to be contributed to public affairs or institutional communication literature, thereby enabling the institutions to adapt to the paradigm changing in today’s conditions and be effective and successful in communication processes.In this sense, our study is composed of two parts, the first designed to redefine the concept of ‘feedback’ in the context of literature review, and the second intended to develop the concept of ‘feedforward’, forming the essence of the study, and to contribute to this concept authentically.On the scale of the accuracy of theoretical propositions that feedback facilitates the two-way communication by opening the channel of communication, that it secures a proactive behaviour by showing the future message and that it can be used as a means of environment scanning by reporting the change, the benefits provided to the field by this concept are tested by seeking for answers to the survey questions within the scope of case study method. Accordingly, it has been concluded that theoretical propositions of the concept of ‘feedforward’ are confirmed in the study in which the intention is to test its accuracy by analysing the dialogues over the popular discussion community of a global institution serving and acting in the sector of informatics.
Keywords: Corparate CommunicationTwo-Way Communication; Çift Yönlü İletişim; Feedback; Geribildirim; Halkla ilişkiler; Hedef Kitle Feedforward; İleribildirim; Kurumsal İletişimTek Yönlü İletişim; One-Way Communication Target Groups; Public relations